The effect of home-based low-volume, high-intensity interval training on cardiorespiratory fitness, body composition and cardiometabolic health in women of normal body mass and those with overweight or obesity: protocol for a randomized controlled trial - Emmanuel Frimpong; Chloe Dafkin; Janine Donaldson; Aletta Maria Esterhuyse Millen; Rebecca Mary Meiring (BMC, 2019)
Abstract Background There is a high prevalence of women in South Africa with overweight and obesity which is associated with an increased risk of cardiometabolic disorders. Perceived barriers such as lack of time and motivation reduce engagement in beneficial activity behaviours for health. High-intensity interval training (HIIT) is a time-efficient and effective way to improve cardiometabolic risk profile regardless of a loss in body mass or change in body composition. This randomized controlled trial aims to determine the effects on cardiorespiratory fitness, body composition and cardiometabolic health and feasibility of a home-based 14-week HIIT program in women with overweight/obesity or normal body mass. Methods One hundred and twenty women (18-40 years old) with a body mass index between 20 and 35 kg/m2, will be stratified according to their BMI (normal, BMI 20-24.9 kg/m2; or high BMI ≥25 kg/m2) and randomized into a HIIT exercising group (HIIT) or a non-exercising control group (CON). HIIT participants will perform exercises for 11 min/session six times per week for a period of 14 weeks. The 2 × 4 HIIT protocol will require a work phase of own-body weight exercise lasting 2 minutes (85% VO2peak), repeated four times and separated by a one-minute active rest phase (65% VO2peak). CON participants will be asked to maintain their normal habitual lifestyle. Outcomes of cardiorespiratory fitness, body composition, echocardiography, central blood pressure, arterial stiffness and biomarkers of cardiometabolic health will be measured before and after the 14-week intervention. Every 4 weeks during the intervention, an objective estimation of compliance to the study protocol will be assessed by measuring participant physical activity over 7 days using an Actigraph GT3X accelerometer. Discussion Supervised laboratory-based HIIT interventions are effective in improving cardiometabolic health. More pragmatic exercise protocols may however show to be successful for mitigating barriers to the engagement in physical activity and exercise resulting in positive benefits to health. Investigation into home-based HIIT regimens are important in women, where globally the rising trend of overweight and obesity overshadows that of men. The results from this study may therefore inform future research on effective exercise prescription for women's health. Trial registration Pan African Clinical Trial Registry (www.pactr.org - id no: PACTR201806003434299), 6th June 2018.